Formação do professor para inclusão escolar de alunos com transtorno do espectro autista e seus efeitos na prática docente - Frade, Paula Nascimento (2018)
In recent years, Inclusive Education has gained a prominent role in teacher education, but there is still a need to expand professional qualification to meet the specificities of school inclusion. Thus, it is possible to notice that the current teacher training, to meet the demands of inclusion, needs to be reviewed. The present research aimed to evaluate the impact of a training action program, on pedagogical practices in inclusion, related to autism spectrum disorder (ASD) for a primary school teacher. The research was carried out, based on a case study, in a municipal school, in São Paulo, in a 5th grade class, that had a student diagnosed with ASD. The work was carried out in four phases. In fase one, an identification questionnaire was used. In fase two, a guidance script for the semi-structured interview with the teacher took place, together with a free observation of the classes, to analyze the teaching practice with the student in inclusion condition. The third phase included a training action program for the teacher, about ASD inclusion. The fourth and last phase included an interview and observation of the post-training classes. The data were qualitatively analyzed, based on the four phases of the study. The analyzes consisted of an interview with the teacher, to get a deeper understanding about her knowledge of the inclusion of ASD students. We also analyzed the classes observations of the pre and post-action training program, post-training interview with the teacher in order to know if there were changes regarding their understanding and pedagogical practice regarding the inclusion of ASDs. The results showed that, according to the observations, made prior to the training program, neither the pedagogical practice of the teacher, nor the interaction of the student with the colleagues was compatible with his needs and there were no activities adapted for him. During the training program, the teacher could rethink her practice and was able to resignify her classes, making proposals that included the student academically and socially. In conclusion, the training program offered to the teacher, proved to be viable (executable) and effective, regarding to the school inclusion of the student with ASD.